Neonatal Sepsis and Inflammatory Mediators - Juliana Reis Machado; Danilo Figueiredo Soave; Marcos Vinícius da Silva; Liliana Borges de Menezes; Renata Margarida Etchebehere; Maria Luiza Gonçalves dos Reis Monteiro; Marlene Antônia dos Reis; Rosana Rosa Miranda Corrêa; Mara Rúbia Nunes Celes (Mediators of Inflammation)
Neonatal sepsis is a major cause of morbidity and mortality and its signs and symptoms are nonspecific, which makes the diagnosis difficult. The routinely used laboratory tests are not effective methods of analysis, as they are extremely nonspecific and often cause inappropriate use of antibiotics. Sepsis is the result of an infection associated with a systemic inflammatory response with production and release of a wide range of inflammatory mediators. Cytokines are potent inflammatory mediators and their serum levels are increased during infections, so changes from other inflammatory effector molecules may occur. Although proinflammatory and anti-inflammatory cytokines have been identified as probable markers of neonatal infection, in order to characterize the inflammatory response during sepsis, it is necessary to analyze a panel of cytokines and not only the measurement of individual cytokines. Measurements of inflammatory mediators bring new options for diagnosing and following up neonatal sepsis, thus enabling early treatment and, as a result, increased neonatal survival. By taking into account the magnitude of neonatal sepsis, the aim of this review is to address the role of cytokines in the pathogenesis of neonatal sepsis and its value as a diagnostic criterion.